Fiscal reforms during fiscal consolidation: The case of Italy - Giampaolo Arachi; Valeria Bucci; Ernesto Longobardi; Paolo Panteghini; Maria Laura Parisi; Simone Pellegrino; Alberto Zanardi (Center for Economic Studies and ifo Institute (CESifo), 2012)
In this paper we aim to discuss the strengths and weaknesses of the fiscal consolidation package adopted recently by the Italian Government in order to achieve a balanced budget by 2013. Revenues are forecasted to increase by more than 3.3 GDP percentage points; these stem mostly from indirect and property taxation. The analysis of the Italian case is interesting since it seems to be consistent with a recent strand of the literature which, in order to foster both short and long-term economic growth, advocated a shift of the tax burden from capital and labour income to consumption and property. Through a set of micro simulation models, this paper evaluates the effects of the Italian fiscal package on households and firms. We show that, in respect of households' income, indirect and property tax reforms are highly regressive, whilst the reform makes limited resources available for growth enhancing policies (reduction in the effective corporate tax burden). Then, we propose an alternative fiscal package. We show that a less regressive reform on households can be obtained by shifting taxation from personal and corporate income tax to indirect taxation. Our proposal allows the tax burden on firms to be reduced substantially and, in the meantime, offers lower personal income tax rates on households in the lowest deciles of income distribution since they are penalized most by the increase in indirect taxation.
Keywords: H20; D22; D31; 330; tax reforms; fiscal consolidation; micro simulation models; Italy; Steuerreform; Haushaltskonsolidierung; Steuerinzidenz; Mikrosimulation; Italien